Sistem Penjualan Online Spare Part Mobil Di Toko Citra Abadi Motor Semarang - Robby Rachmatullah; Rudi Yanto - STMIK AUB Surakarta (APMMI - Asosiasi Profesi Multimedia Indonesia, 2013)
Abstract - Current usage of Internet services as a means to obtain information more widely used. Because of extensive coverage, the Internet is ideal when used as a promotional tool and a means to publish information. The objective of this program is to promote web companies as well as providing services to the customers regarding the purchase of spare parts on-line. Internet is a medium that is potential to develop an information system that is dynamic and wide-ranging, with any information on the internet can be obtained easily and quickly. Based on the various facilities and their role of being owned by the internet then developed a